Handbook of Metaheuristic Algorithms: From Fundamental Theories to Advanced Applications - Tsai, Chun-Wei; Chiang, Ming-Chao (Uncertainty, Computational Techniques, and Decision Intelligence, 2023)
Handbook of Metaheuristic Algorithms: From Fundamental Theories to Advanced Applications provides a brief introduction to metaheuristic algorithms from the ground up, including basic ideas and advanced solutions.